NATIONAL MENTALITY OF KAZAKHSTAN: TRADITIONS AND MODERNITY (Journal of Philosophy Culture and Political Science, 2022)
The article is devoted to an actual scientific problem - the study of the mentality of an ethnic group. Analysis of mentality today is carried out in different directions, using a variety of techniques. The nature of the mentality, the features of its formation and functioning are investigated, the dominant features of the mentality of the people are revealed. The article highlights the most common features of the Kazakh mentality. In this article, the authors conduct research on the national mentality of Kazakhstan on the basis of Kazakh philosophy, forms of culture, as well as the features of its manifestation. The purpose of this article is to determine the factors in the formation of the national mentality and the connection with the national identity of citizens. Definition of basic categories needed for further research. An important aspect is the study of not only the Kazakh mentality, but Kazakhstani in general. The main factors of influence are the historical aspect, traditions, language, informational metabolism. One of the main aspects is the study of nomadism as the basis of the existence of the Kazakh people. Which in turn are the main values of modern society. The authors of the article classify the formation of the Kazakh society, which served as the formation of the national mentality. Folklore reflects the everyday worldview of the people in different eras, being a source of non-theoretical wisdom. It is characterized by a focus on understanding the existence of a person in the world, which is the connection with philosophy.Key words: mentality, national mentality, national identity, existence, Kazakh philosophy, culture.